Biochemical variability in selected ginger (Zingiber officinale Rosc.) germplasm accessions - JOHNSON K GEORGE, A SHAMINA, T JOHN ZACHARIAH, B SASIKUMAR (Journal of Spices and Aromatic Crops, 1997)
Twenty five accessions of ginger (Zingiber officinale) germplasm were studied for variations in total free amino acids, proteins, total phenols and isozymes. Considerable variations were observed for total free amino acids, proteins and total phenols. The variability for the isozyme loci in the population was geuerally low. Dendrograms were prepared based on the average similarity of the accessions with respect to the isozyme profiles and accessions collected from the same geographical area had a tendency to cluster together.